Kerjasama Kepala Madrasah dan Guru dalam Meningkatkan Mutu Pembelajaran di Madrasah Ibtidaiyah Al-Khairaat Kotarindau - Muhammad Nur Iman; Moh. Nur (Peneliti.net, 2020)
This article discusses the cooperation between the principal and the teachers in improving the quality of learning in the Al-Khairaat Islamic Elementary School, Kotarindau, a subdistrict of Dolo, Sigi regency. The main problems of this article are How is the cooperation among the principal and the teachers in improving the quality of learning in the Al-Khairaat Islamic Elementary School, Kotarindau, a subdistrict of Dolo, Sigi regency? What are the factors that support the cooperation between the principal and the teachers in improving the quality of learning in this school? This research uses the qualitative approach those are observation method, interview, and documentation, through reduction analysis, data display and data verification, and then validation of the data. As a result of this research, it shows that the cooperation among the principal and the teachers, in improving the quality of learning in the Al-Khairaat Islamic Elementary School runs well. This is proven by seeing the impacts such as the community’s enthusiasm to enroll their children in this school because they considered that the school has a good quality. Also, this school was chosen as the prime of KKM in the Sigi Regency. Moreover, the supporting factor for the establishment of good cooperation in this school is the principal always instilling important values in cooperating with all elements. These values are including mutual openness, mutual understanding, and mutual respect.